Access to Endovascular Stroke Care in the US and Implications for Transport Models. (16th November 2020) - Waqas, Muhammad; Aldstadt, Jared; Yasumiishi, Misa; Mokin, Maxim; Levy, Bennett; Rai, Hamid; Chin, Felix; Davies, Jason; Levy, Elad I; Siddiqui, Adnan H
Abstract: INTRODUCTION: Timely access to stroke centers is key to achieving optimal functional outcomes. METHODS: A list of accredited and certified endovascular capable (ECCs) and non-endovascular stroke centers (NECCs) was obtained. US population obtained from Census Bureau was divided into census blocks (each consisting of 2, 500 residents). The proportion of residents with 60-minute access was estimated by previously validated methodology using ArcGIS. We further estimated the proportion of NECCs with an ECC within a 30-minute drive. RESULTS: We included 322 ECCs and 1624 NECCs in our analysis. Overall, 49.6% US residents had 60-minute road access to ECCs. Combined road and air ambulance access were available to 64.8% of residents. About 113 million US residents lack 60-minute ground or air access to ECCs. The median number of stroke centers per 1 million population was 0.73 (IQR 0.4-1.1). About 84.4% residents have 60-minute access to NECCs across the US. The median number of NECCs per 1 million population was 4.5 (IQR 3.2-5.7). Ground only access was available to 77.9%. US population. About 738 of NECCs (45.4%) had an ECCs within 30 minutes of drive time. The number and percentage of NECCs varied between states. CONCLUSION: One-third of the US population lacks timely access to endovascular stroke care. There is a need for new endovascular capable facilities in areas that do not have timely access to endovascular care for stroke. The transport models need to be tailored to each state depending on the location and proximity of existing facilities.